Employment of Abi Nowas in Contemporary Arabic Poetry - گلی , حسین; نويدي , عبدالوحيد (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
A new text has emerged in contemporary Arabic literature, which is the employment of the crystallized literary heritage in the heritage personalities as an expression of the poetic experiences of contemporary poets. In his poetry, he made change and creativity, as an expression of poetic experiences in the circumstances of his own life in the golden age, which was full of luxury living and luxury. There are many contemporary poets who were interested in this modern technique to enrich their literature, including Adonis and Amal Dunqul, hasab alSheikh Jaafar, who were inspired by heritage in their poetic poems employing glimpses of Abu Nowas’ personality to express their own poetic experiences. Nawas in the poems of these poets and their significance through which they expressed their feelings, and to identify the reasons for their tendency to employ this personality to express their experiences in friendship.